While America Sleeps : Self-Delusion, Military Weakness, and the Threat to Peace Today - Kagan, Donald and Kagan, Frederick W., 1970- (New York St. Martin's Press, 2000)
Traces Britain's international and defense policies in the years between World War I and II and studies the how their self-delusion and unwillingness to face their responsibilities affected the world at the start of World War II.
Include Map, Notes, Bibliography and Index
Keywords: Military policy -- National security--Forecasting -- United States -- Great Britain -- Diplomatic relations